Deep Breathing Relaxation Techniques Improve Emotional Control on Tuberculosis Patients - Domianus Namuwali; Fery Agusman Mendrofa; Meidiana Dwidiyanti (International Journal of Public Health Science (IJPHS), 2016)
Tuberculosis is an infectious disease caused by Tuberculosis Mycobacterium. Based on  WHO report in 2014, the world population suffering from tuberculosis were 9.6 million people while in Indonesia it was amounted 324 539 people. Tuberculosis patients have a tendency to experience emotional disturbance due to the illness. A deep breathing relaxation is a nursing action for controlling emotions of tuberculosis patients. The study design is quasi-experimental design with one group pre-test-post-test. Data were collected by using a questionnaire adapted from Gross and John (2003). Data were analyzed using paired t test. The results of this research is deep breathing relaxation technique is effective to control emotions of tuberculosis patients with p value = 0,001.